Image Enhancement Techniques for Liver Ultasound Images - Deshpande Nilkanth Mukund (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Liver is the most important organ of a human body. To human body the function of liver is very important, so as to maintain body healthy. Liver generates different digestive materials which is helpful in digestion. The liver functions may be disturbed due to high variety of circumstances. Due to alcohol consumption, hyper acidity and many other factors, liver damages. There are many abnormalities in liver including liver enlargement, fatty liver, chronic liver failure, formation of cancerous cells, swelling etc. Ultrasound imaging is the most popular and accurate techniques for the investigation of major of the abdominal diseases. Abdominal ultrasonic consists of Gall Bladder, Liver, and Kidney for the analysis. Out of these organs, kidney and liver are very smaller organs. So their ultrasonic investigation could be a critical issue. Another challenge in ultrasonic imaging is the presence of speckle noise. So it is required to work out for an image enhancement technique for liver ultrasonic images. This paper introduces different techniques for the image enhancement of ultrasonic images for liver analysis. The results obtained from these techniques are presented and compared to get conclusion.